Creating Employment in the Middle East and North Africa - Gardner, E. (Pamphlet Series; Pamphlet Series, No., 2003)
The population of the Middle East and North Africa is one of the fastest growing in the world, but jobs have not grown as fast as the region's workforce. This paper addresses questions such as"Can current GDP growth generate more employment, or will higher GDP growth be required?"and "Will the current pattern of job creation-with much of the region's workforce employed by the public sector-need to change?".